Dre Parker's Effort To Be Respected And Not To Be Abused In Karate Kid (2010) Directed By Harald Zwart: An Individual Psychological Approach - SATITI., ALINIA DYAH (2012)
The subject of the study is the novel and the movie Angel and Demon directed by Ron Howard and written by Dan's Brown. The study is about similarities and differences between novel and movie of Angel and Demon. The writer studies in structural approach by comparing the element in the movie and in the novel. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and the novel of Angel and Demon and the secondary data source is information related to the primary data source, website, and book about structural approach and about the novel and movie of Angel and Demon. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. The results of the research show that : first, based on the structural analysis, there are many similarities between the novel and the movie of Angel and Demon The similarities are in character and characterization, setting, and point of view. The difference lays in the aspect of character and characterization, in which the minor character in the movie is merged and blended with the other character.